DEVELOPING MULTIPLICATION FACT FLUENCY - Brendefur, Jonathan; Strother, S.; Thiede, K.; Appleton, S. (Advances in Social Sciences Research Journal, 2015)
Using specific components of three broad learning theories—cognitive, social-interactional, and behavioral—students in 3rd, 4th and 5th grade classrooms were given multiplication fact fluency instruction over a period of five weeks for 10-15 minutes each day. Two different approaches were utilized with two distinct groups of students for the purpose of comparing different approaches to fluency development. Results indicate that students using a strategy-based approach for fluency development by means of instructional tasks emphasizing social-interactional and cognitive theories (particularly Bruner’s theory of Modes of Representation) increased multiplication fact fluency, with a greater degree of consistency, than students using a drill-based approach emphasizing behavioristic techniques such as repetition and memorization.